2006
DOI: 10.1038/sj.cdd.4401915
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB by HDAC inhibitor apicidin through Sp1-dependent de novo protein synthesis: its implication for resistance to apoptosis

Abstract: Histone deacetylase (HDAC) inhibitors are promising anticancer drugs, but these exert differential responses depending on the cell types. Here, we demonstrate a new mechanism for activation of nuclear factor-jB (NF-jB) by HDAC inhibitor apicidin and the role of NF-jB signaling pathway for mediating differential cellular responses, especially, apoptosis. Treatment of HeLa cells with apicidin increases transcriptional activity of NF-jB and its target gene IL-8 and cIAP-1 induction, which involves the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…HDACIs-Previous studies have shown that HDACIs activate NF-B in diverse cell types (11,12,34). To characterize this phenomenon in greater detail, a time course analysis of NF-B activation was conducted (Fig.…”
Section: Induction Of Nf-b Activity and Regulation Of Ros Bymentioning
confidence: 99%
“…HDACIs-Previous studies have shown that HDACIs activate NF-B in diverse cell types (11,12,34). To characterize this phenomenon in greater detail, a time course analysis of NF-B activation was conducted (Fig.…”
Section: Induction Of Nf-b Activity and Regulation Of Ros Bymentioning
confidence: 99%
“…The discrepancy may be due to the activation of NF-κB by BST204 in HT-29 cells, which is essential for cell survival, because BST204 was able to activate the transcription of NF-κB reporter gene (unpublished data). Consistent with our observation, NF-κB activation has been demonstrated to contribute to resistance of cancer cells to apoptotic potential of HDAC inhibitor apicidin which has been shown to be a potent anti-proliferative agent Kim et al, 2006a;2006b;Eun et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…DNMT1 knockdown induces the activation of capase-3, resulting in subsequent cleavage of PARP (Figure 7c). However, treatment of HeLa cells with apicidin does not cause cleavages of neither caspase-3 nor PARP (Figure 7c), consistent with our previous observation showing that apicidin does not induce apoptosis of HeLa cells (Kim et al, 2006). The results suggest that DNMT1 might be a good target for inducing apoptosis of HeLa cells.…”
Section: Knock Down Of Dnmt1 Induces Expression Of P21supporting
confidence: 81%